Increased levels of interleukin-33 in gingival crevicular fluids of patients with chronic periodontitis - Saglam, Mehmet; Koseoglu, Serhat; Aral, Cuneyt Asm; Savran, Levent; Pekbagriyanik, Tugba; Cetinkaya, Ayse (2023)
The purpose of this clinical study is to comparatively investigate the interleukin-33 (IL-33) levels in gingival crevicular fluid (GCF), saliva and plasma of patients with periodontal disease as well as periodontally healthy subjects and the association between these levels and clinical parameters. GCF, saliva and plasma samples were collected from systemically healthy, non-smoker chronic periodontitis patients (CP group, n = 20), gingivitis patients (G group, n = 20) and periodontally healthy control groups (H group, n = 20). Full-mouth clinical periodontal parameters were also recorded. IL-33 levels were determined by ELISA. The total amount of GCF IL-33 was greater in the G and CP groups compared to the H group (p < 0.05). The GCF IL-33 concentration was significantly lower in the CP group than in the H and G groups (p < 0.001). Salivary or plasma IL-33 levels were similar in the study groups. The total amount of GCF IL-33 was positively correlated with the GI, PI and BOP (%) (p < 0.05). Considering the present findings, the increase in total amounts of GCF IL-33 may have a role in the pathogenesis of periodontal disease.
Keywords: Liquido Crevicular Gingival; Interleucina-33; Enfermedades Periodontales; Plasma; Saliva